Multifunctional Evaluation and Spatio-temporal Evolution Analysis of Cultivated Land in Guangdong Province - Junmei ZANG; Xiao FU; Shengxiang LIU; Hui LI (Guangdong nongye kexue)
【Objective】The study aims to investigate the spatio-temporal dynamics of cultivated land use functions in 21 prefecture-level cities in Guangdong Province, and to promote the sustainable utilization of cultivated land resources and optimal allocation of cultivated land use functions in Guangdong Province.【Method】Taking the 21 prefecture-level cities in Guangdong Province as the evaluation units, we constructed a multifunctional index system of cultivated land, and adopted entropy weight method and comprehensive index evaluation method to evaluate the cultivated land use functions in Guangdong Province from 2005 to 2020.【Result】In terms of overall changes, the level of each function of cultivated land in Guangdong Province from 2005 to 2020 is not high, the agricultural production function and economic contribution function of cultivated land are at a lower level as a whole, the other functions are at a general level as a whole, and only the ecological security function is at a higher level in 2005 and 2015. In terms of overall structure, the structure of each function of cultivated land in Guangdong Province from 2005 to 2020 is relatively stable, with a small fluctuation; the ecological safety function of cultivated land accounts for the highest proportion, and the agricultural production function accounts for the lowest proportion. In terms of the spatio-temporal evolution of sub-functions, the spatio-temporal pattern of each function of cultivated land in Guangdong Province has changed significantly during the period of 2005-2020. In the time dimension, the agricultural production function, social security function, and ecological safety function of cultivated land show an overall decreasing trend, and the food security function, economic contribution function, and landscape recreation function of cultivated land show an overall increasing trend. In the spatial dimension, the spatial patterns of the social security function and economic contribution function of cultivated land change greatly, while the changes in spatial patterns of the other functions are more stably.【Conclusion】The comprehensive function of cultivated land in Guangdong Province is weak, and the differences in cultivated land use functions in different cities are obvious. In the future, diversified and differentiated policies for the protection and utilization of cultivated land can be adopted according to local conditions, which will provide references for the development of regional control rules for the utilization of territorial space in Guangdong Province in the new era, the selection of key areas for comprehensive land improvement, and the delineation of permanent basic farmland and other natural resources utilization and management practices.